Hysteretic DC electrowetting by field-induced nano-structurations on polystyrene films - Sawane, Yogesh B.; Datar, Suwarna; Ogale, Satishchandra B.; Banpurkar, Arun G. (Soft Matter, 2015)
Electrowetting (EW) offers executive wetting control of conductive liquids on several polymer surfaces. We report a peculiar electrowetting response for aqueous drops on a polystyrene (PS) dielectric surface in the presence of silicone oil. After the first direct current (DC) voltage cycle, the droplet failed to regain Young's angle, yielding contact angle hysteresis, which is close to a value found in ambient air. We conjecture that the hysteretic EW response appears from in situ surface modification using electric field induced water-ion contact with PS surface inducing nano-structuration by electro-hydrodynamic (EHD) instability. Atomic force microscopy confirms the formation of nano-structuration on the electrowetted surface. The effects of molecular weight, applied electric field, water conductivity and pH on nano-structuration are studied. Finally, the EW based nano-structuration on PS surface is used for the enhanced loading of aqueous dyes on hydrophobic surfaces.